2008
DOI: 10.1292/jvms.70.1121
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa Morphology during the Breeding Season in Thoroughbred Stallions in Japan

Abstract: ABSTRACT. The morphology of spermatozoa of modern Thoroughbred stallions in Japan was investigated during the breeding season. A total of 299 semen samples were collected from the penises of 16 stallions immediately after service. The rate of abnormalities in sperm heads and tails, spermatozoa with cytoplasmic droplets and slides with medusa cells to total observed slides in each stallion were 3.9 ± 2.1%, 11.5 ± 5.9%, 2.4 ± 2.6% and 20.1%, respectively. The values for the area, length, width and aspect ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The morphology of equine spermatozoa has been reported to reflect the quality [6,7,8, 14, 18,19,20]. Jasko et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of equine spermatozoa has been reported to reflect the quality [6,7,8, 14, 18,19,20]. Jasko et al .…”
mentioning
confidence: 99%
“…Differences in sperm morphology have been reported between the four seasons of the year [7, 16], but little is known about the changes in sperm morphology throughout the breeding season itself. In Thoroughbred stallions in Japan, we previously found that the morphology of the sperm head varies during the breeding season [14]. …”
mentioning
confidence: 99%